HUBUNGAN KONSEP DIRI DENGAN KOMPETENSI SOSIAL PADA SISWA KELAS VIII MTs AD-DA’WA BEKASI TAHUN PELAJARAN 2006-2007 - Neneng Yuliana; Ujang Rohman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
Based on phenomena in grade 8 students in Mts. AdDa’wa Bekasi, there are few students that tend to draw themselves from interpersonal relation with students at their age outside their peer group. Many question then arise, if there were any significant reason and its correlation between their self concept and social competency. The method used for this research is a correlation model with sample population of 80 subject participant. The data required for this research then gathered with questionnaire and were measured with self concept measurement test TSCB (Tennessee Self Concept Scale) from William H. Fist. Other measurement test were then created based on Krasnor Theory to measure social competency from those students. After data have been collected with we have a correlation point rs=0,598 with thit = 6,59 > ttab =1,980 which means that H1 is approved and H0 is denied. According to result of this research, it was concluded that the assumption were proved true that there is positive relation between self concept and social competency in grade 8 students from Mts. AdDa’wa Bekasi.